Improved Timing Estimation Using Iterative Normalization Technique for OFDM Systems - Suyoto Suyoto; Iskandar Iskandar; Sugihartono Sugihartono; Adit Kurniawan (Institute of Advanced Engineering and Science, 2017)
Conventional timing estimation schemes based on autocorrelation experience performance degradation in the multipath channel environment with high delay spread. To overcome this problem, we proposed an improvement of the timing estimation for the OFDM system based on statistical change of symmetrical correlator. The new method uses iterative normalization technique to the correlator output before the detection based on statistical change of symmetric correlator is applied. Thus, it increases the detection probability and achieves better performance than previously published methods in the multipath environment. Computer simulation shows that our method is very robust in the fading multipath channel